The presence of Pessoa : English, American, and Southern African literary responses - Monteiro, George (Studies in Romance languages (Lexington, Ky.), 1998)
Fernando Pessoa (1888--1935) is perhaps the most engaging of the great Western modernists of this century. Born in Portugal but raised and educated in southern Africa, Pessoa wrote poetry, fiction, and nonfiction. George Monteiro provides refreshingly new interpretations of Pessoa's Mensagem (Message) and the modernist novella 0 Banqueiro Anarquista (The Anarchist Banker). But he is primarily interested in tracing Pessoa's influence on a wide range of contemporary writers. Among those Monteiro finds putting Pessoa's work to their own surprising -- and sometimes comic -- uses are Joyce Carol.